Varying social media post types differentially impacts engagement in a behavioral weight loss intervention. Issue 4 (6th August 2014) - Hales, Sarah B.; Davidson, Charis; Turner-McGrievy, Gabrielle M.
Abstract: The purpose of this study was to examine whether different types of posts differentially affect participant engagement and if engagement with social media enhances weight loss. Data are a subanalysis from a randomized weight loss study with a 4-month follow-up support period via private Facebook groups and monthly meetings. Counselors posted five different post types/week based on social cognitive theory (weight-related, recipes, nutrition information, poll votes, or requests for suggestions). Types of participant engagement (likes, comments/poll votes, and views) were assessed. Poll votes were the most engaging (mean number of votes or comments/poll 14.6 ± 3.4, P < 0.01) followed by suggestions (9.1 ± 2.7 posts, P < 0.01) and weight-related posts (7.4 ± 3.1 posts, P < 0.01). Engagement with Facebook was significantly associated with weight loss during the 4-month maintenance period ( B = −0.09, P = 0.04). The findings provide evidence for ways to provide social support during weight loss interventions using remote methodology.